An Atom‐Economical Approach to 2‐Triazolyl Thio‐/Seleno Pyridines via Ruthenium‐Catalyzed One‐pot [3+2]/[2+2+2] Cycloadditions. Issue 23 (24th October 2019) - Bhatt, Divya; Singh, Prasoon Raj; Kalaramna, Pratibha; Kumar, Krishn; Goswami, Avijit
Abstract: An efficient method to access 2‐triazolyl thio‐/selenopyridines with good to excellent yields by ruthenium(II)‐catalyzed one‐pot [3+2]/[2+2+2] cycloaddition reactions of azides, 1‐alkynyl thio‐/selenocyanates and 1, 6‐diynes is reported. This atom‐economical catalytic strategy offers a mild and practical approach to access a variety of such cycloadducts with good to excellect regioselectivities. The protocol was further extended to the synthesis of 3, 3′‐bis(triazolyl thio‐/seleno)‐2, 2′‐bipyridines by the reaction of tetraynes with 1‐alkynyl thio‐/selenocyanates in the presence of aryl/alkyl azides. Abstract :